Inhibition of dengue virus infection by 1‐stearoyl‐2‐arachidonoyl‐phosphatidylinositol in vitro. Issue 12 (22nd October 2019) - Sanaki, Takao; Wakabayashi, Masato; Yoshioka, Takeshi; Yoshida, Ryu; Shishido, Takao; Hall, William W.; Sawa, Hirofumi; Sato, Akihiko
Abstract : Dengue fever is an acute febrile infectious disease caused by dengue virus (DENV). Despite the significant public health concerns posed by DENV, there are currently no effective anti‐DENV therapeutic agents. To develop such drugs, a better understanding of the detailed mechanisms of DENV infection is needed. Both lipid metabolism and lipid synthesis are activated in DENV‐infected cells, so we used lipid screening to identify potential antiviral lipid molecules. We identified 1‐stearoyl‐2‐arachidonoyl‐phosphatidylinositol (SAPI), which is the most abundant endogenous phosphatidylinositol (PI) molecular species, as an anti‐DENV lipid molecule. SAPI suppressed the cytopathic effects induced by DENV2 infection as well as the replication of all DENV serotypes without inhibiting the entry of DENV2 into host cells. However, no other PI molecular species or PI metabolites, including lysophosphatidylinositols and phosphoinositides, displayed anti‐DENV2 activity. Furthermore, SAPI suppressed the production of DENV2 infection‐induced cytokines and chemokines, including C‐C motif chemokine ligand (CCL)5, CCL20, C‐X‐C chemokine ligand 8, IL‐6, and IFN‐β. SAPI also suppressed the TNF‐α production induced by LPS stimulation in macrophage cells differentiated from THP‐1 cells. Our results demonstrated that SAPI is an endogenous inhibitor of DENV and modulated inflammatory responses in DENV2‐infected cells, at least in part via TLR 4.—Sanaki, T., Wakabayashi, M., Yoshioka, T., Yoshida, R., Shishido, T., Hall, W. W., Sawa, H., Sato, A. Inhibition of dengue virus infection by 1‐stearoyl‐2‐arachidonoyl‐phosphatidylinositol in vitro. FASEB J. 33, 13866‐13881 (2019). www.fasebj.org